2019
DOI: 10.1001/jama.2019.4973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aclidinium Bromide on Major Cardiovascular Events and Exacerbations in High-Risk Patients With Chronic Obstructive Pulmonary Disease

Abstract: IMPORTANCE There is concern that long-acting muscarinic antagonists increase cardiovascular morbidity or mortality in patients with chronic obstructive pulmonary disease (COPD). OBJECTIVE To determine the cardiovascular safety (noninferiority) and efficacy (superiority) of aclidinium bromide, 400 μg twice daily, in patients with COPD and cardiovascular disease or risk factors. DESIGN, SETTING, AND PARTICIPANTS Multicenter, randomized, placebo-controlled, double-blind, parallel-design study conducted at 522 sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 30 publications
(80 reference statements)
3
50
0
Order By: Relevance
“…Mortality was defined by all-cause mortality or cardiovascular death. MACE were defined as cardiovascular death, non-fatal myocardial infarction, or non-fatal stroke (Wise et al, 2019 ). Heart failure was defined as Killip ≥ 2 (Cenko et al, 2019 ), or definitions from each trial were used ( Table 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mortality was defined by all-cause mortality or cardiovascular death. MACE were defined as cardiovascular death, non-fatal myocardial infarction, or non-fatal stroke (Wise et al, 2019 ). Heart failure was defined as Killip ≥ 2 (Cenko et al, 2019 ), or definitions from each trial were used ( Table 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…55 Furthermore, AB has low systemic exposure, hence, minimising typical LAMA AEs 44,56,57 and the recently conducted ASCENT-COPD clinical trial that specifically enrolled patients with elevated cardiovascular risk found no increase in cardiovascular risk with AB. 58…”
Section: Tolerabilitymentioning
confidence: 99%
“…Assessment of sudden or unwitnessed death is a particularly difficult problem in COPD populations since some of these deaths may be the result of respiratory events as well as cardiovascular death. 5 In line with previous adjudication committees, 1 3 , 14 we used arbitrary definitions of sudden death in the absence of a presenting acute illness and relied upon interviews with family or caretakers to help in this process. Among 320 deaths finally adjudicated as sudden death, only 189 (59%) were reported as such by site investigators.…”
Section: Discussionmentioning
confidence: 99%